"When did you decide to receive the Covid-19 vaccine?" Survey in a high-volume vaccination center - Marion Le Maréchal; Amina Batel; Stéphanie Bouvier; Hajer Mahdhaoui; Morgane Margotton; Jean-Philippe Vittoz; Etienne Brudieu; Christine Chevallier; Pierrick Bedouch; Saber Touati; Olivier Epaulard (Taylor & Francis Group, 2021)
Highly efficient and safe Covid-19 vaccines are available in Europe in amounts that theoretically allow for a high immune coverage. However, a notable proportion of the population is reluctant toward immunization. We aimed to determine, among people who chose to be vaccinated, when they made the decision and whether they would have preferred an earlier vaccination. A survey was conducted in a high-volume Covid-19 vaccination center in France from 28 May to 9 July 2021 through an anonymous questionnaire. The 2519 participants (54.1% males; median age 39 years) attributed lower efficacy and safety to Covid-19 vaccines than to vaccines in general. When asked when they decided to receive the vaccine, 15.5% and 16.0% answered "less than one month ago" and "less than one week ago," respectively; age <40 and female sex were independently associated with these responses. When asked whether they would have preferred to have been vaccinated earlier, 57.6% answered "definitely no," "rather no," or "neither yes nor no"; female sex (independently from age) was associated with these answers. When asked whether they would have preferred to receive the vaccine as early as January 2021, 65.2% answered "definitely no," "rather no," or "neither yes nor no"; age <40 and female sex were independently associated with these responses. In conclusion, one-third people had made the decision to be vaccinated only recently, while more than half would not have preferred an earlier vaccination, in particular women and those aged <40 years. Vaccine campaigns should take such short-term decision-making processes into account.